Pengembangan Dashboard Monitoring Berbasis Web untuk Transparansi Program Makanan Bergizi Gratis di Indonesia - Kholid Sholeh Anwar; Rian Afandi Saputra; Bagus Sutrisno; Anisatul Azizah; Arief Budiman (LPPM Universitas Merdeka Madiun, 2026)
The development of information technology has encouraged the use of web-based systems to transparently monitor and display data. The Free Nutritional Meals Program in Indonesia requires a robust monitoring system, given the large volume of data involved and its distribution across many regions. However, the manual monitoring process has led to delays and a lack of transparency. This study aims to develop a web-based monitoring dashboard to enhance the program's effectiveness and transparency. The prototype method used consists of several stages: requirements gathering, prototype creation, evaluation, and system improvement. The study shows that the dashboard can display data in a direct, systematic, and easily understandable way. This system helps make the monitoring process more efficient and facilitates decision-making. This study concludes that a web-based monitoring dashboard can be an effective way to increase transparency and improve implementation of the Free Nutritional Meals Program in Indonesia.